The Effect of Type II DM on the Incidence of Sensorineural Deafness at Bali Royal General Hospital - Agus Santosa; I Wayan Sulistiawan (Warmadewa University, 2022)
Type II diabetes mellitus (DMT II) is a major health threat, and DM is known to be associated with sensorineural deafness. Age, duration of DM, hypertension and hypertriglycerides are believed to influence this process. This study aims to determine the relationship between type II DM and the incidence of sensorineural hearing loss at Bali Royal General Hospital. The study used a case control design which was carried out on patients admitted between July-September 2021 at Bali Royal General Hospital. The sampling technique employed in the DMT II group with sensorineural deafness was total random sampling, while for comparison, simple random sampling was used. The analyses were carried out by descriptive analysis, chi square test for bivariate data, and logistic regression test for multivariate analysis. The p value is said to be meaningful if <0.05. The whole process of data analysis in this study used SPSS.sav 25. The number of samples was 8 patients with an average age of 49.62 ± 8.45. The mean of RBS (Random Blood Sugar) sugar was 152.25±60.92 mg/dL, and FBS (Fasting Blood Sugar) was 87.87±14.09 mg/dL. Patients with low FBS values ​​and diabetes duration of <5 years had more normal hearing conditions in the right ear (60%), while patients with high FBS and diabetes duration of ≥5 years had more SNHL (66.7%). However, the two conditions did not show a statistically significant relationship (p>0.05). The results of multivariate analysis found that there was no significant relationship between FBS levels and age with hearing conditions in the left ear (p> 0.05). In this study, there was no significant relationship between FBS, duration of DM, pattern of drug consumption, age, and hypertension status of DM patients with the incidence of SNHL in the right and left ears. Keywords: Type II diabetes mellitus, sensorineural deafness, hearing loss